2004
DOI: 10.1074/jbc.m313602200
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli Transcriptional Regulator MarA Directly Represses Transcription of purA and hdeA

Abstract: The Escherichia coli MarA protein mediates a response to multiple environmental stresses through the activation or repression in vivo of a large number of chromosomal genes. Transcriptional activation for a number of these genes has been shown to occur via direct interaction of MarA with a 20-bp degenerate asymmetric "marbox" sequence. It was not known whether repression by MarA was also direct. We found that purified MarA was sufficient in vitro to repress transcription of both purA and hdeA. Transcription an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 41 publications
1
41
1
Order By: Relevance
“…Regulation of the hdeAB operon. The figure has been produced using data from the literature (8,13,16,20,22,24,26,27,30,33,37,39,42,43,44,46) as well as the results obtained in this study. Thick arrows represent genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regulation of the hdeAB operon. The figure has been produced using data from the literature (8,13,16,20,22,24,26,27,30,33,37,39,42,43,44,46) as well as the results obtained in this study. Thick arrows represent genes.…”
Section: Resultsmentioning
confidence: 99%
“…2). MarA is known to bind a "marbox" partially overlapping the Ϫ35 hexamer of the promoter (37). Therefore, competition with RNA polymerase for DNA binding and/or direct interactions between MarA and 70 , 38 , or other subunits of RNA polymerase are possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4). Although AraC-like regulators are commonly activators of transcription, several AraClike regulators have been identified that function as both activators and repressors, including MarA in E. coli (32), YbtA (4), and PchR (11). Also similar to the repression of mtrF by MtrR, MpeR-dependent repression had no effect on the TX-100 induction of mtrF expression (Fig.…”
mentioning
confidence: 85%